Implementasi Pelaksanaan Program Gerakan Literasi Sekolah (GLS) Selama Pembelajaran Tatap Muka Terbatas SDN Polehan 2 Malang - Dina Elistiana Permata Sari; Muh Arafik; Titis Angga Rini; Dina Elistiana Permata Sari; Muh Arafik (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: This study aims to describe the implementation, infrastructure and facilities used, constraints, and solutions in the implementation of the GLS program during PTMT at SDN Polehan 2 Malang. The scope of this research is the implementation of GLS grades 2-5 at SDN Polehan 2 Malang which will be held in the even semester of the 2021/2022 academic year. This study uses a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that the implementation of the GLS program at SDN Polehan 2 Malang as long as PTMT has been regularly carried out every day according to the stages. Literacy activities begin with a 10-15 minute reading habituation stage or other activities and are accompanied by activities responding to reading either through question and answer activities regarding reading materials that have been read or others. The infrastructure and facilities at SDN Polehan 2 Malang is limited because the school is still under construction and there are several classes that are still in new condition so they do not have a reading corner. The implementation of offline literacy is still carried out in the classroom. There are several obstacles in implementing the GLS program offline and online. Although there are several obstacles in its implementation, there are also various solutions to overcome these obstacles.. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan, prasarana dan sarana yang digunakan, kendala, dan solusi dalam pelaksanaan program GLS selama PTMT di SDN Polehan 2 Malang. Ruang lingkup penelitian ini yaitu pelaksanaan GLS kelas 2-5 di SDN Polehan 2 Malang yang dilaksanakan pada semester genap tahun ajaran 2021/2022. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa Pelaksanaan program GLS di SDN Polehan 2 Malang selama PTMT sudah teratur dilakukan setiap hari sesuai tahapannya. Kegiatan literasi dimulai dengan adanya tahap pembiasaan membaca 10-15 menit ataupun kegiatan lain dan disertai adanya kegiatan menanggapi bacaan baik melalui kegiatan tanya jawab mengenai bahan bacaan yang telah dibaca maupun lainnya. Prasarana dan sarana di SDN Polehan 2 Malang ini terbatas karena sekolah masih dalam tahap pembangunan dan ada beberapa kelas yang masih dalam kondisi baru sehingga belum memiliki sudut baca. Pelaksanaan literasi secara offline masih dilaksanakan di dalam kelas saja. Terdapat beberapa kendala dalam pelaksanaan program GLS secara offline dan online. Meskipun terdapat beberapa kendala dalam pelaksanaannya, terdapat pula berbagai solusi dalam mengatasi kendala-kendala tersebut.